2019
DOI: 10.1002/adfm.201902274
|View full text |Cite
|
Sign up to set email alerts
|

Contiguous and Atomically Thin Pt Film with Supra‐Bulk Behavior Through Graphene‐Imposed Epitaxy

Abstract: We investigate the stable atomic configuration and the nature of chemical bonding in epitaxial Pt films on graphene. Graphene-templated monolayer to few-multilayers of Pt, synthesized as contiguous 2D films by room temperature electrochemical methods, is shown both experimentally and computationally to exhibit stable {100} structure in the 1-2 layer range. The fundamental question being investigated is whether surface Pt atoms rendered in these 2D architectures are as stable as those of their counterparts in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 37 publications
2
36
2
Order By: Relevance
“…Following the discovery of graphene, 1 derivatives of graphene are intensely appealing to numerous research domains owing to their distinctive behaviors, such as tunable electrical conductivity, [2][3][4][5] excellent mechanical properties, [6][7][8] high corrosion resistance, 9-11 extremely efficient electrocatalytic activity 12,13 and so forth. 10 These unique properties depend on the lateral dimension and thickness of the synthesized graphene sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Following the discovery of graphene, 1 derivatives of graphene are intensely appealing to numerous research domains owing to their distinctive behaviors, such as tunable electrical conductivity, [2][3][4][5] excellent mechanical properties, [6][7][8] high corrosion resistance, 9-11 extremely efficient electrocatalytic activity 12,13 and so forth. 10 These unique properties depend on the lateral dimension and thickness of the synthesized graphene sheets.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical states of the surface component were determined by XPS to observe changes in d-band center position, as an indication on strain induced on Pt atoms [32][33][34] .…”
Section: Resultsmentioning
confidence: 99%
“…The prevention of interdiffusion led to the preservation of Pt surface at elevated temperatures, which is important for fuel cells operated at 80 °C or higher. They further investigated strain and ligand effects in the presence of graphene interlayer . Extended X-ray absortion fine structure (EXAFS) showed that compressive strain (ca.…”
Section: Core–shell Electrocatalystsmentioning
confidence: 99%
“…They further investigated strain and ligand effects in the presence of graphene interlayer. 154 Extended X-ray absortion fine structure (EXAFS) showed that compressive strain (ca. 3%) was induced on Pt ML epitaixally grown on graphene/Au substrate.…”
Section: Core−shell Electrocatalystsmentioning
confidence: 99%